Mexico : Selected Issues and Analytical Notes. - International Monetary Fund. Western Hemisphere Dept. (Washington, D.C. : International Monetary Fund, 2017)
This Selected Issues paper assesses the economic impact of Mexico's structural reforms. The Mexican authorities have been implementing an ambitious structural reform agenda in a coordinated effort to lift productivity growth. The reforms have targeted a broad range of industries; dissolved state monopolies; and addressed labor market, education, and governance shortcomings. The analysis suggests that external headwinds have masked evidence that the reforms are achieving many of the intended transformations in the targeted sectors. Priority should go to reforms targeting the rule of law and attendant improvements in security and reduction of corruption. These will not only improve the business environment but are key to the success of existing reform efforts.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet